Clinical value of neutrophil to lymphocyte ratio in the region of lower extremity deep venous thrombosis - Akgul, Engin; Bircan, Nurhayat; Yumun, Gunduz; Vural, Ahmet Hakan (The European Research Journal, 2017)
Objectives. Many studies have demonstrated a significant association between cardiovascular disease and neutrophil to lymphocyte ratio (NLR). To our knowledge, no study has been reported in patients with deep venous thrombosis (DVT) which affecting proximal or distal leg. In this study we analyzed proximal and distal DVT according to the NLR. Methods. This retrospective study was obtained from patients’ records of a tertiary university hospital between May 2011 to January 2014. A total of 57 patients with the diagnosis of acute primary DVT and 30 patients as control group included in the study. All of them were confirmed with lower extremity venous duplex examinations. Of these, 37 examinations with the diagnosis of proximal DVT were compared to 20 examinations with distal DVT. The groups compared regarding to complete blood counter values. Results. Mean eosinophil level was higher in the distal DVT group (0.28±0.24 vs. 0.12±0.01, p=0.001), whereas median NLR were higher in the proximal DVT group than the distal DVT group (3.5 [0.5-4.3] vs. 2.3 [1.2-9.7], respectively; p=0.002). In addition, median NLR, leukocyte and neutrophil counts were statistically lower in the control group than the others (p=0.014, p=0.027 and p=0.004, respectively). Conclusion. NLR, an inexpensive and easily measurable laboratory variable, was independently and significantly associated with the presence and severity of DVT, especially acute proximal DVT.